Traffic Counting Case Study on Teuku Nyak Arief Road - Fathiah Fathiah; Fauzan Adhima (JOURNAL OF INFORMATICS AND COMPUTER SCIENCE, 2018)
Banda Aceh is one of the most touristic cities that rely on transportation mode for everyday needs from bicycle, motorcycle, car and public transportation. The population growth of Banda Aceh city increased from year to year causing an imbalance between the amount of transportation on the highway and the available capacity of roads. This causes a variety of traffic problems So that required activities Monitoring the flow of traffic on a particular road to know the smooth flow of traffic. Hence from it came the idea to design a traffic counting system that can calculate the amount of traffic flow of vehicles As a guide to be used as information flow of traffic.This system was created using Microsoft Visual Studio, and Open Source Computer Vision. The result of testing this system using video files that have been recorded on the road Teuku Nyak Arief Banda Aceh. This program as a whole shows the success of more than 80% .With this system is expected to make it easier to calculate the number of vehicles on the road. Keywords: Number of Vehicles, Traffic Flows, Microsoft Visual Studio and Open Source Computer Vision